Digitalisasi Sistem Posyandu Ternak untuk Meningkatkan Produksi Peternakan di Desa Gumantar Kabupaten Lombok Utara - Rohim, Abdul; Zahira, Dayana; Abdi, Wahyu Indra; Maulida, Siska; Rosida, Abidatur; Dewi, Apriani Puspita; Amali, Haswadi; Supardan, Supardan; Robiyansa, Robiyansa; Fikri, Haekal; Budiharta, Agus; Seyarano, Guran Lampa; Rosyidi, Muhammad Subhan Bahruddin; Gusairi, Muhammad (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2024)
Gumantar Village, located in Kayangan District, North Lombok Regency, is the only underdeveloped village in West Nusa Tenggara Province. After the 2018 earthquake, this village experienced severe impacts. Economic recovery after the Covid-19 pandemic and the Foot and Mouth Disease (FMD) outbreak gave rise to an initiative in the form of POSYANDU LIVESTOCK. Gumantar Village formed this institution with community cadres as the front guard for livestock services, especially ruminants. The ORMAWA HMP3IP PPK program played a role in the formation of this institution, which was inaugurated by the Head of the NTB Provincial Service on November 15 2022. Since the formation of the Livestock Posyandu, livestock management in villages has improved significantly, involving aspects of feed, waste, livestock management, health services, and artificial insemination technology . However, communication and services are still manual, encouraging the need for innovation. Therefore, a website-based application was created as a solution to improve livestock posyandu cadre services. The program is also focused on strengthening cadre capacity through training and collaboration with the local government, with the aim of creating superior human resources in posyandu as the village's front guard in dealing with livestock problems, increasing productivity and achieving farmer welfare.